THEMATIC PRIORITIES FOR CONTINUING EDUCATION IN MENTAL HEALTH FROM THE PERSPECTIVE OF HEALTH WORKERS - Lima, Helder de Pádua; Machado, Cynthia Fernanda Teles; Britto, Ana Carolina Saggin; Rozza, Soraia Geraldo; Costa, Maria Antonia Ramos; Souza, Verusca Soares de (Cogitare Enfermagem, 2024)
Objective: To find out the thematic priorities for continuing education in mental health from the perspective of workers in the Unified Health System. Method: an exploratory and qualitative study was carried out with 37 health workers from a municipality in Mato Grosso do Sul, in September 2022. Data was collected using a self-administered individual questionnaire and a focus group, guided by a semi-structured script of questions. The material was subjected to thematic content analysis. Results: The themes ’Humanization in mental health care’, ’Mental health in the context of primary care’, ’Management of crises’, and ’Mental health of health workers and professional valorization’ emerged as priorities for continuing education actions in mental health. Conclusion: Knowledge of these thematic priorities makes it possible to plan continuing education actions based on the daily problems experienced by health workers.